alguem me ajuda
5(×+1)-3(×+2)=0
Garibelson:
Aff ficou bugado
Soluções para a tarefa
Respondido por
0
Fazendo a distributiva:
![5(x + 1) - 3(x + 2) = 0 5(x + 1) - 3(x + 2) = 0](https://tex.z-dn.net/?f=5%28x+%2B+1%29+-+3%28x+%2B+2%29+%3D+0)
![5x + 5 - 3x - 6 = 0 \\ 5x - 3x = + 6 - 5 \\ 2x = 1 \\ x = \frac{1}{2 \\ x = 0.5 5x + 5 - 3x - 6 = 0 \\ 5x - 3x = + 6 - 5 \\ 2x = 1 \\ x = \frac{1}{2 \\ x = 0.5](https://tex.z-dn.net/?f=5x+%2B+5+-+3x+-+6+%3D+0+%5C%5C+5x+-+3x+%3D++%2B+6+-+5+%5C%5C+2x+%3D+1+%5C%5C+x+%3D++%5Cfrac%7B1%7D%7B2+%5C%5C+x+%3D+0.5)
Respondido por
1
Olá
5(x + 1) -3(x + 2) = 0
5x + 5 - 3x - 6 = 0
5x - 3x = 6 - 5
2x = 1
x = 1/2
Resposta: x = 1/2
Bons estudos
Perguntas interessantes
Matemática,
9 meses atrás
Administração,
9 meses atrás
Português,
9 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás